Elites, Elitism, and Community in the Archaic Polis. Issue 3 (9th July 2018) - Ma, John
Abstract : This article explores the famously diverse and expressive political cultures of the "Archaic" Greek communities (650 – 450 BCE) in the light of recent work on public goods and publicness, to which the present essay partly responds. This contribution may also be considered as a fragment of the long history of the Greek polis . The distinction between "elitist" or "aristocratic" styles and "middling" or "popular" styles, upon closer examination, turns out to be a set of political play-acting gestures, predicated on different political institutions and notably on access to public goods. The "middling" styles paradoxically reflect restricted political access, while "aristocratic" competition in fact responds to the stress and uncertainties of broad enfranchisement. The whole nexus of issues and gestures surrounding distinction is hence not socially autonomous, but immediately linked to political requirements and institutional pressures. This article thus argues not just for the centrality of public goods to polis formation in early Greece, but also for the centrality of formal access and entitlements to the "public thing"—in other words, for the centrality of the state and its potential development. Putting the "state" back in the early history of the Greek city-state: the exercise has its own risks (notably that of teleology), but it attempts to avoid problems arising in recent histories of the polis, where the state is downplayed or indeed dismissed altogether, and the polis itself reduced to a pure phenomenon of elite capture or elite constitution.